2014
DOI: 10.1103/physrevd.89.016017
|View full text |Cite
|
Sign up to set email alerts
|

Light dark matter anomalies after LUX

Abstract: The landscape of dark matter direct detection has been profoundly altered by the slew of recent experiments. While some have claimed signals consistent with dark matter, others have seen few, if any, events consistent with dark matter. The results of the putative detections are often incompatible with each other in the context of naive spin-independent scattering, as well as with the null results. In particular, in light of the conflicts between the DM interpretation of the three events recently reported by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 60 publications
5
96
0
Order By: Relevance
“…For the vector models, which contribute to the spin-independent cross section σ SI , we follow the usual convention mapping onto this quantity defined at zero relative velocity. For pseudo-scalar interactions, we compute the integrated cross section for DM scattering with a nucleon by integrating over the recoil energy of the nucleus and the velocity of the DM, which we assume follows a Maxwellian distribution, using techniques developed in [74][75][76][77], (specifically using the code presented in Ref. [76]).…”
Section: B Direct Searchesmentioning
confidence: 99%
“…For the vector models, which contribute to the spin-independent cross section σ SI , we follow the usual convention mapping onto this quantity defined at zero relative velocity. For pseudo-scalar interactions, we compute the integrated cross section for DM scattering with a nucleon by integrating over the recoil energy of the nucleus and the velocity of the DM, which we assume follows a Maxwellian distribution, using techniques developed in [74][75][76][77], (specifically using the code presented in Ref. [76]).…”
Section: B Direct Searchesmentioning
confidence: 99%
“…As LUX experiment [11] currently imposes the most stringent bound on DM, one necessarily considers DM that has negligible interaction with the Xenon nucleus. Recent studies after the LUX result [17][18][19]27] have shown that the isospin-violating DM is still compatible with one of positive signals, those of the CDMS-II Si experiment.…”
Section: Jhep05(2014)086mentioning
confidence: 99%
“…alternatives (e.g., modified halo models) or varying assumptions about the Xenon scintillation efficiencies [17][18][19]. A scenario that still remains viable in reconciling some of these results is the isospin-violating DM [20][21][22][23][24][25][26].…”
Section: Jhep05(2014)086mentioning
confidence: 99%
“…Different WIMP-nucleus scattering models will correspond to different nuclear responses, which often include a sum of responses contributing, and can also lead to interference terms between the responses [7,27,28]. A study of a variety of spin-1/2 dark matter UV complete models whose responses are described by these non-standard responses was given in [10], and a general survey of simplified models of spin-0, spin-1/2, and spin-1 dark matter models was carried out in [29]. There exist additional nuclear responses beyond these five, but are typically not considered due to P and CP properties of the nuclear ground state and an assumption of CP conservation of the interaction.…”
Section: A Non-relativistic Eft Wimp-nucleus Scatteringmentioning
confidence: 99%
“…Additional nuclear responses were identified that augment the standard SI and SD responses. Though these operators induce nuclear recoil energy spectra that differ from the traditional SI/SD models [9], the upper limits on the WIMP-nucleon cross section are not strongly affected, except for experiments with relatively high recoil energy thresholds, greater than tens of keV [10].…”
Section: Introductionmentioning
confidence: 99%